2003
DOI: 10.1063/1.1542683
|View full text |Cite
|
Sign up to set email alerts
|

Formation and structure of inverted hexagonal pyramid defects in multiple quantum wells InGaN/GaN

Abstract: We have determined the structure of inverted hexagonal pyramid defects (IHPs) in multiple quantum wells InGaN/GaN by high-angle annular dark-field scanning transmission electron microscopy (HAADF STEM). HAADF STEM images reveal definitely that the IHP nucleates at a threading dislocation and grows in the form of a thin six-walled structure with InGaN/GaN {101̄1} layers. It has been found that IHPs start even at In-rich dots under adverse growth conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 25 publications
3
48
1
Order By: Relevance
“…4(a) and (b). These images support very strongly the previous observations, 8,14,15) the images for which were somewhat obscure, and completely deny the model 11,12,16) that the main InGaN QWs end abruptly at the surfaces of the pits and the pits are then filled by the GaN capping layer with no InGaN/GaN sidewall layers. The InGaN and GaN sidewall layers were epitaxially grown successively on the six {10 1 11} planes during the MWQ deposition, each of them forming by the layer-by-layer growth similar to the growth on the (0001) planes.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…4(a) and (b). These images support very strongly the previous observations, 8,14,15) the images for which were somewhat obscure, and completely deny the model 11,12,16) that the main InGaN QWs end abruptly at the surfaces of the pits and the pits are then filled by the GaN capping layer with no InGaN/GaN sidewall layers. The InGaN and GaN sidewall layers were epitaxially grown successively on the six {10 1 11} planes during the MWQ deposition, each of them forming by the layer-by-layer growth similar to the growth on the (0001) planes.…”
Section: Resultssupporting
confidence: 79%
“…For the analysis of the structure details of V defects, the present specimen with the thick QWs and barriers compares favorably with the In 0:2 Ga 0:8 N (2.5 nm)/ GaN (8 nm) MQW that was used in a previous experiments. 8,14,15) HAADF-STEM images give rise to strong contrast dependence on the atomic number so-called Zcontrast, unlike CTEM images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 6 is a typical [10][11][12] cross-sectional dark-field TEM image of AlInGaN epilayer and underlying GaN template layer. It can be seen that each pit is associated with a threading dislocation from the underlying GaN template layer at its vertex.…”
Section: Resultsmentioning
confidence: 99%
“…While p-InGaN hole injection and contact layers are beneficial for the improvement of luminescence and electrical forward bias characteristics, the InGaN layer often shows, depending on thickness and composition of InGaN, a surface morphology with a high density of pits related to the formation of V-defects (also called inverted hexagonal pyramids), which have been proven to be associated with threading dislocations at their apexes. [9][10][11][12][13] It has been suggested that these pits act as a path for reverse leakage current. 14 In this study, in order to improve the surface morphology and electrical properties of the green LEDs, we developed an InGaN:Mg/GaN:Mg shortperiod superlattice (SPSL) to be used for p-type hole injection and contact layers.…”
Section: Introductionmentioning
confidence: 99%